Recognizing Mental Retardation Early: Detection and Intervention Strategies - Rilta Mardalena; Asra, Yulita Kurniawaty (Jurnal Psikologi Terapan, 2025)
This research confirms that although individuals with intellectual disabilities face significant challenges, they still have developmental potential that can be enhanced through appropriate support and intervention. This research aims to evaluate the effectiveness of interventions on a child with intellectual disabilities who is following a therapy program at the Insan Cemerlang Duri Foundation. The writer used an experiment with a single-subject design (Single Case Experimental Design), which allows for in-depth observation of changes in the subject's behavior before and after treatment. The subject of the study was "DZ", a 15year old boy with limitations in intellectual and communication abilities. Result Showed that DZ was still very dependent on parental assistance in daily activities, but began to show an understanding of simple instructions that were often repeated. The interventions provided focused on basic skills training and improving functional communication. The implications of this research are the importance of an inclusive environment, family involvement, and the use of individual experimental designs in developing interventions that are responsive to the unique needs of children